Inside Cover: Onocerin Biosynthesis Requires Two Highly Dedicated Triterpene Cyclases in a Fern Lycopodium clavatum (ChemBioChem 4/2016). (February 2016) - Araki, Takeshi; Saga, Yusuke; Marugami, Momo; Otaka, Junnosuke; Araya, Hiroshi; Saito, Kazuki; Yamazaki, Mami; Suzuki, Hideyuki; Kushiro, Tetsuo
Abstract : The inside cover picture shows the biosynthesis of an unique symmetrical triterpene α‐onocerin produced by a fern Lycopodium sp. Two genes, LCC and LCD, were identified that belong to oxidosqualene cyclase (OSC) family. LCC exclusively utilized dioxidosqualene (top) as a substrate to produce a half cyclized intermediate pre‐a‐onocerin (middle) which was then taken up by LCD to produce α‐onocerin (bottom). The substrate specificity of these enzymes was significantly different from known OSC family that uncovered the potential ability of this family to catalyze even more different reactions. More information can be found in the communication by T. Kushiro et al. onpage 288 in Issue 4, 2016 (DOI:10.1002/cbic.201500663 ).